Intraspecific variation and micro-macroevolution connection: illustration with the late Miocene genus Progonomys (Rodentia, Muridae). Issue 4 (8th April 2010) - Lazzari, Vincent; Aguilar, Jean-Pierre; Michaux, Jacques
Abstract : Recent progresses in our knowledge of mouse odontogenesis have enhanced rodent tooth morphology as a model for Evo-Devo studies. Deciphering the connection between macroevolution and microevolution, however, especially in the case of mammalian teeth, requires examples to illustrate how morphological differences among species, or higher taxa, can stem from population-level processes. In this paper we use paleontological material to study intraspecific variation of tooth morphology in the late Miocene species Progonomys clauzoni, over a short span of geological time in a restricted area. Progonomys is of particular interest as a stem genus of all murine rodents (Old World rats and mice). We use morphometrical and statistical methods to illustrate how change in the amplitude in variation at the population level through geological time is associated with the emergence of new characters. Some of these new characters, including functional ones, become fixed in parallel in distinct murine lineages. Nine million years ago, Progonomys clauzoni displayed variational properties of the developmental system shared by the Murinae, which can also explain some singular tooth characteristics that now are scattered among the diverse lineages. Further morphometric studies, however, are necessary to explain how the variety of cusp patterns observed in Progonomys clauzoni can be explained by developmental properties.